Analisis Unsur Sosial dan Budaya dalam Novel Laskar Pelangi Karya Andrea Hirata - Fransiska Andrea Poa; Katharina Woli Namang (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research aims to analyze the social and cultural elements contained in the novel Laskar Pelangi by Andrea Hirata. As a literary work that reflects the reality of life in the Belitong Malay community, this novel contains various social values, such as solidarity, the importance of education, and social inequality, as well as cultural values, including local traditions, religiosity, and local wisdom. The research uses a qualitative descriptive method with content analysis techniques. The research results show that the novel Laskar Pelangi not only presents an inspiring story about the struggle for education, but also becomes a medium for preserving and representing the social and cultural identity of the Belitong Malay community. This makes this novel relevant as study material in understanding the social and cultural dynamics of Indonesian society.